Stress Reduction Training Based on Mindfulness Method to Enhance Self-control Among Rehabilitation Patient in Orbit Hospital, Surabaya : Stress Reduction Training Based on Mindfulness Method to Enhance Self-control Among Rehabilitation Patient in Orbit Hospital, Surabaya - Maya Vratasti, I Gusti Ayu; Alrbertina, Christina (Journal of Research and Measurement in Psychology: JPPP, 2021)
ABSTRACT Rehabilitation member of Rumah Sehat Orbit Surabaya (RSOS) experienced problems in self-control based on preliminary data collection through interviews process. These problems inhibit the recovery process of rehabilitation members from using drugs. Member of rehabilitation need to improve self-control in order to maximize the recovery process during the rehabilitation and be able to maintain the behavior not to relapse using drugs after rehabilitation. Several studies show that mindfulness based stress reduction (MBSR) is effective in increasing self-control. This study aims to examine the effect of mindfulness based stress reduction (MBSR) training to improve self-control in members of the Rumah Sehat Orbit Surabaya (RSOS). The research method used is experiment. Participants in this study were 11 people. Participants scores will be compare before and after the intervention is given. Based on the result of this research through comparative test, the significance results of 0.004 (<0.05) on self-control and 0.011 (<0.05) on mindfulness. It means that there is significant difference before and after mindfulness based stress reduction (MBSR) training. Practicing mindfulness consistenly helps individuals to be able to look inside themselves and recognize their abilities so that individuals feel they have control over themselves.